Harmonizing Halal Entrepreneurship in Yogyakarta's Warmindo Ventures: Insights from the Kuningan Community - Putri Rizka Citaningati; Kamaluddin Kamaluddin; Tri Alfianto (University of Merdeka Malang, 2024)
This study explores the entrepreneurial landscape of Warmindo ventures established by the Kuningan community in Yogyakarta, Indonesia, with a particular focus on the perspective of Sharia entrepreneurship. The research explores the motivations, strategies, and success factors behind these ventures, considering both the entrepreneurs' aspirations and the perceptions of their primary customer base, namely the students of Universitas Islam Indonesia (UII). Drawing upon a combination of field research and literature review, the study employs qualitative descriptive methods, including in-depth interviews with Warmindo entrepreneurs and UII students. The comparative analysis juxtaposes the findings with existing literature on conventional and Islamic entrepreneurship, shedding light on the alignment between economic goals and religious values among the Kuningan community entrepreneurs. The results indicate a prevailing focus on material prosperity among Warmindo entrepreneurs, with limited attention to spiritual fulfillment or adherence to Sharia principles in their business practices. Conversely, UII students exhibit a nuanced perspective, emphasizing the importance of ethical business conduct and the integration of religious values in economic endeavors. Despite the stagnancy observed in the entrepreneurs' economic goals, there is potential for growth and alignment with Sharia principles through increased awareness and education on Islamic entrepreneurship.